Investment lending within the small and medium enterprise financial support program - M.A. Khudomaka; L.O. Aksonova (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет, 2021)
The article considers the issues of investment lending for small and medium business development programs. It is determined that at all levels of management and credit activities of banks, the implementation of such programs should be a priority. The key basis of the study is the statement that the effectiveness of small and medium business development fully depends on the built system of affordable lending. Qualitatively new approaches to financing investment programs from various sources, in particular, cheap bank loans and state support, need to be introduced. The analysis of recent publications indicates the need to implement innovative financial instruments and financing methods that comprehensively take into account the risks of all participants. The paper analyzes the state of bank investment lending to small and medium enterprises. The problems that arise during the implementation of the program to support such business, namely - the risks of non-performing loans, lack of financial resources to repay loans; problems with legal servicing of credit debts, lack of sufficient credit collateral, non-compliance of borrowers with the terms of the program, etc. Domestic banks today have a number of programs to promote small and medium enterprises in relation to the development of investment activities, but the tools for their implementation have a number of significant shortcomings. They do little to help reduction of investment risks of business; do not affect the simplification of the credit system and the availability of resources. It is proposed to solve the problems of small and medium business investment, to carry out a balanced strategy of state support, which in the complex will take into account the specific operating conditions and risks of such enterprises. Financial support for investment programs for small and medium enterprises, both by banks and the state, should provide the full range of financial and credit instruments for real rather than declarative solutions to certain problems.